Wolfram syndrome: A rare case report - Anitha Padmanabhan; Aditi Parihar; Urmi S C. Vartak; Nitin M Gadgil (Wolters Kluwer Medknow Publications, 2019)
We present an autopsy case of a 19 year old male admitted for breathlessness and oliguria. He was diabetic since 7 years of age and was on insulin. Patient was on testosterone and anti hypertensives. He was diagnosed of hypocontractile bladder and congenital bilateral megaureter with vesico-ureteric reflux 2 years back. History of hemiparesis 2 years back. CT scan of the brain showed a right fronto- parietal healed infarct. At autopsy, bilateral kidneys showed coarse granularity and scarring. Pelvicalyceal system and both ureters were dilated. A right sided intrabdominal testes was identified. On histology, kidney showed features of diabetic nephropathy and pancreas showed decreased number of islet cells. Correlating the clinical, laboratory and autopsy parameters, our case satisfies the EURO-WABB criteria (1major+2minor) for diagnosis of Wolfram Syndrome, even though genetic confirmation could not be done.[1],[2]